Entacapone alleviates muscle atrophy by modulating oxidative stress, proteolysis, and lipid aggregation in multiple mice models - Zeng, Rong; Xu, Hanbing; Wu, Mingzheng; Zhou, Xianlong; Lei, Pan; Yu, Jiangtao; Wang, Pinyi; Ma, Haoli; Zhao, Yan (Frontiers in Physiology, 2024)
BackgroundSkeletal muscle atrophy significantly affects quality of life and has socio-economic and health implications. This study evaluates the effects of entacapone (ENT) on skeletal muscle atrophy linked with oxidative stress and proteolysis.MethodsC2C12 cells were treated with dexamethasone (Dex) to simulate muscle atrophy. Four murine models were employed: diaphragm atrophy from mechanical ventilation, Dex-induced atrophy, lipopolysaccharide (LPS)-induced atrophy, and hyperlipidemia-induced atrophy. Each model utilized entacapone (10 mg/kg), with sample sizes: Control (9), MV (11), MV + ENT (5) for diaphragm atrophy; Control (4), Dex (4), Dex + ENT (5) for Dex model; Control (4), LPS (4), LPS + ENT (5) for LPS model; and similar for hyperlipidemia. Measurements included muscle strength, myofiber cross-sectional area (CSA), proteolysis, oxidative stress markers [uperoxide dismutase 1 (SOD1), uperoxide dismutase 2 (SOD2), 4-hydroxynonenal (4-HNE)], and lipid levels.ResultsOur findings confirm Dex-induced muscle atrophy, evidenced by increased expression of muscle atrophy-associated proteins, including Atrogin-1 and Murf-1, along with decreased diameter of C2C12 myotubes. Atrogin-1 levels rose by 660.6% (p < 0.05) in the Dex group compared to control, while entacapone reduced Atrogin-1 by 84.4% (p < 0.05). Similarly, Murf-1 levels increased by 365% (p < 0.05) in the Dex group and were decreased by 89.5% (p < 0.05) with entacapone. Dexamethasone exposure induces oxidative stress, evidenced by the upregulation of oxidative stress-related proteins Sod1, Sod2, and 4-HNE. Entacapone significantly reduced the levels of these oxidative stress markers, enhancing GSH-PX content by 385.6% (p < 0.05) compared to the Dex-treated group. Additionally, ENT effectively reduced the Dex-induced increase in MDA content by 63.98% (p < 0.05). Furthermore, entacapone effectively prevents the decline in diaphragm muscle strength and myofiber CSA in mice. It also mitigates diaphragm oxidative stress and protein hydrolysis. Additionally, entacapone exhibits the ability to attenuate lipid accumulation in the gastrocnemius muscle of hyperlipidemic mice and alleviate the reduction in muscle fiber CSA.ConclusionOur findings suggest that entacapone is a promising therapeutic candidate for muscle atrophy, functioning through the reduction of oxidative stress, proteolysis, and lipid aggregation. Future research should explore the underlying mechanisms and potential clinical applications of entacapone in muscle-wasting conditions.